EVALUASI SISTEM PROTEKSI PETIR EKSTERNAL PADA GEDUNG KULIAH TERPADU KAMPUS UIN IMAM BONJOL PADANG DI SUNGAI BANGEK - Mondrizal, Mondrizal; Kamil, Insannul (Jurnal Teknologi dan Vokasi, 2025)
Protection and security in building structures are very much needed against lightning strikes. Integrated Lecture Building of UIN Imam Bonjol Padang Campus in Sungai Bangek whose building construction is located in a highland area in a hilly area. For that, an external lightning protection system is needed to protect the building from direct lightning strikes. In designing external lightning protection installed on building structures, it must follow the technical requirements that need to be considered, such as identifying the need for a PUIPP-based lightning protection system, determining the level of protection of the lightning protection system based on SNI 03-7015-2004, IEC 1024-1-1, and NFPA 780. The lightning protection system used in this building is Lightning Protection Radius 120 m Non Radio Active as an external defense of the electromagnetic or electrostatic field system. Based on the ground resistance measurement data at several grounding points, the values ​​​​are 1.48 ohms, 1.35 ohms and 1.34 ohms which are still below the standard value of a maximum of 2 ohms required. The evaluation of the discussion can describe the protection area of ​​the Integrated Lecture Building with the results obtained showing that the building protection already has a good level of efficiency and is included in ideal conditions with a safe category from lightning strike protection referring to the measurement data of the soil resistance value at several grounding points which are used as a grounding system.